Sufism Study in Communication Perspective - Muttaqien; T. Faizin; Saidaturrahmah; Muhammad Khalidin; Rossa Alfira (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2019)
Sufism is one of the fields of Islamic studies that focus on cleansing the spiritual aspects of humans, which in turn leads to noble morals. Through this study of Sufism one can find out about ways to do self-cleaning and practice correctly. From this knowledge it is hoped that he will appear as someone who is good at controlling himself when he interacts with others, or when carrying out activities that require honesty, sincerity, responsibility, trust and others. If viewed from the perspective of humans as limited beings, Sufism can be defined as an effort to purify self by way of distancing the influence of world life will focus attention only on Allah. Sufism comes from the Qur'an and Sunnah although in its development it was influenced by foreign elements. Sufism has developed since the end of the second century Hijri, although in the first century the hijri had been seen in the ascetic life form (zuhud) practiced by the Prophet and the ma'rifah sahabatuan. There are several approaches in Sufism study, thematic approach, figure study approach and combination approach. The main figures and works in the study of Sufism include Imam Al-Ghazali with his momental work Ihya ‘Ulum al-Din, Ibn Arabi with his work Al-Futuhat al-Makkiyah and Fushush al-Hikam and others mentioned earlier. The latest development of Sufism stems from the thought of Fazlur Rahman with the concept of neo sufism. In Indonesia, Hamka has featured the term modern Sufism in his book "Modern Sufism". If Al-Ghazali requires uzlah in the exploration of the quality of nature, then Hamka actually wants a true truth seeker to remain active in various aspects of people's lives.